PENGARUH PERBEDAAN POLA CUACA TERHADAP ANGKA KEJADIAN DEMAM BERDARAH DENGUE DI KOTA PONTIANAK PADA PERIODE 2008 DAN 2009 - ., Chung Andirius (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background. Dengue Hemorrhagic Fever (DHF) is and still one of the important transmitted diseases problems in Indonesia. Weather patternmay influence mosquito life cycle hence it role in DHF epidemic. Thusknowing the impact of differing weather pattern to DHF incidence may helpformulating the correct prevention steps. Objective. To see the generalpattern of weather in Pontianak from 2008 to 2009 and to see theirinfluences in DHF incidence. Methods. This cross-sectional analytic studyis using secondary data from Agency for Meteorology, Climatology andGeophysics and Pontianak City Health Offices. Result. The majority ofDHF incidence in 2008 and 2009 occured in months with highertemperature value than the preceding months. There is strong correlationbetween DHF incidence in Pontianak with ambient temperature value (p<0.05), But there is no correlation between DHF incidence and Rainfallindex value (p > 0.834 and 0.524). Conclusion. The weather pattern in2009 had higher temperature and sparser rainfall than 2008. Thisconditions at 2009 triggered a higher DHF risk in Pontianak City. Keyword: DHF, weather pattern, Aedes aegypti.1). Medical School, Medical Faculty, Universitas Tanjungpura,Pontianak, West Kalimantan.2). Department of Nutrition, Medical Faculty, Universitas Tanjungpura,Pontianak, West Kalimantan.3). Department of Parasitology, Medical Faculty, UniversitasTanjungpura, Pontianak, West Kalimantan.